Comparisons of therapeutic effects of levodopa, levodopa and selegiline, and bromocriptine in patients with early, mild Parkinson's disease: three year interim report. Parkinson's Disease Research Group in the United Kingdom. (1993)
OBJECTIVE--To determine the optimum treatment for early Parkinson's disease. DESIGN--An open, long term, prospective randomised trial conducted by the Parkinson's Disease Research Group of the United Kingdom. SETTING--93 hospitals throughout the United Kingdom. SUBJECTS--782 patients with early Parkinson's disease who were not receiving dopaminergic treatment. INTERVENTIONS--Patients allocated to treatment with levodopa/dopa decarboxylase inhibitor alone (arm 1), levodopa/decarboxylase inhibitor/selegiline in combination (arm 2), or bromocriptine (arm 3). MAIN OUTCOME MEASURES--Disability assessment as judged by improvement on Hoehn and Yahr, modified Webster, and North Western University disability scales. Adverse event profile and mortality ratios. RESULTS--Interim results indicate that all three treatment regimens led to improvement in baseline disabilities after 12 months' treatment and that deterioration in control was apparent by three years. No significant differences were found between the results of treatment in arm 1 and arm 2, but both were significantly more effective than bromocriptine (arm 3) and had fewer early adverse reactions. The adjusted difference (95% confidence interval) in Webster rating for arm 3 v 1 was 0.93 points (0.27 to 1.50; p = 0.0058) and for arm 3 v 2 was 1.25 points (0.61 to 1.89; p = 0.0002). The incidence of dyskinesias and motor oscillations, however, was significantly lower in arm 3 (2% and 5%, respectively) than in arm 1 (27% and 33%, respectively) and arm 2 (34% and 35%, respectively). CONCLUSIONS--As there were no marked differences in functional improvement between the three groups the choice of treatment in the early stages of Parkinson's disease may not be critical.